Illinois Occupational Skill Standards Surgical Technologist. - Illinois Occupational Skill Standards and Credentialing Council, Carbondale; Illinois Occupational Skill Standards and Credentialing Council, Carbondale ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1999)
This document, which is intended to serve as a guide for workforce preparation program providers, details the Illinois occupational skill standards for programs preparing students for employment as surgical technologists. The document begins with a brief overview of the Illinois perspective on occupational skill standards and credentialing, the process used to develop the skill standards, and assumptions underlying the standards. Presented next are skill standards for 49 tasks typically performed by surgical technologists in the preoperative, intraoperative, and postoperative phases of treatment. Each skill standard statement contains the following components: (1) the actual skill standard (including the conditions of performance, work to be performed, and performance criteria); (2) performance elements and assessment criteria; and (3) a recommended assessment and credentialing approach. The following are among the tasks for which skill standards are provided: obtain appropriate sterile and unsterile items for procedures; maintain highest standards of aseptic technique during procedures; and assist with preparing operating rooms for subsequent patients. Appended are the following: glossary; lists of Illinois Occupational Skill Standards and Credentialing Council, Health and Social Sciences Subcouncil, and Surgical Technologist Standards Development Committee members; Health and Social Sciences Subcouncil Surgical Technologist Standards recognition proposal; and a list of necessary workplace skills. (MN)
Availability: Curriculum Publications Clearinghouse, Western Illinois University, Horrabin Hall 46, 1 University Circle, Macomb, IL 61455-1390, Tel: 800-322-3905, Fax: 309-298-2869, e-mail: CPC@wiu.edu (#509d, $7). For full text: http://www.standards.siu.edu/pdf/health/surgtech.pdf.
Sponsoring Agency: Illinois State Board of Education, Springfield.
ERIC Note: For other Illinois Occupational Skill Standards, see CE 080 474-492.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Advisory Committees; Allied Health Occupations Education; Competence; Competency Based Education; Definitions; Education Work Relationship; Educational Benefits; Educational Needs; Educational Objectives; Educational Principles; Employment Potential; Employment Qualifications; Equipment Maintenance; Equipment Storage; Equipment Utilization; Evaluation Criteria; Glossaries; Guidelines; Job Analysis; Job Skills; Labor Force Development; Medical Services; Occupational Clusters; Performance Based Assessment; Postsecondary Education; Program Guides; Sanitation; Secondary Education; State Standards; Statewide Planning; Student Certification; Student Evaluation; Surgery; Surgical Technicians; Two Year Colleges; Vocational Education; Illinois; Guides, Non-Classroom.; Legal/Legislative/Regulatory Materials